Analisis Pembelajaran Pendidikan Agama Islam (PAI) pada Pembentukkan Akhlak Siswa Kelas IV Sekolah Dasar Negeri III Sukaslamet Indramayu - Silmi Rafiatul Mursalin; Moch. Hasyim Fanirin; Anjar Sulistyani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Learning Islamic Education is a conscious effort carried out by teacher in the form of preparation for students to know, understand, and practice the Islamic teachings that have been studied, through conselling, guiding, or training activities in order to achieve the goals setting. In the subject of Islamic education, we could find the topics focussing on the formation of students’ morals. This study aims to describe the implementation of Islamic Religious Education learning and determine the values ​​of social attitudes during the learning at State Elementary School or SD Negeri III Sukaslamet.This study is qualitative research. The data of the study is collected from interviewing students, conducting the observation and having documentation. This study adopts a purposive sampling technique to take samples.The study reveals that the feedback method is used in the implementation of Islamic religious education learning. And appropriate strategies are formulated as well to convey the material to students. And the study indicates that values ​​of honesty, courtesy, trustworthiness, respect for others, and obedience to parents are found in the learning of Islamic religious education.